Concentration - determination of the relevant market – theory and practice in the Republic of Serbia - Zarić, Vlade; Vasiljević, Zorica; Petković, Danijela (Economics of Agriculture, 2010)
Identifying of the concentration level on certain markets is a starting point in the analysis of market structures. This is also a prerequisite for subsequent decision making at the institutional level and estimating state policy effects on the market. Concentration and its effects on competition are determined by taking into account the relevant products and relevant market. It is generally accepted that competition is desirable and that it has positive effects. Fair competition results in lower production costs and lower product prices, and stimulates innovation as well. Analysis of concentration provides information about the intensity of competition. Despite the importance of concentration, in domestic literature these issues are not often found. One reason is the lack of complete institutional arrangements for this area. This paper presents the theoretical principles of concentration determination and shows the practice in the Republic of Serbia.